Springback prediction of mild steel sheet on 60° air bending - Mohd Zuhairi, Md Zohir (2010)
This report deals with the deformation of a spring-back on 60° air bending. Now days,research and study have been done on a spring-back. In sheet metal bending, a flat part is bent using a set of punches and dies. In this thesis, punches and die are referred to as tools. The punch and the dies are mounted on a press brake, which control the relative motion between the punch and die and provides the necessary bending pressure. In this thesis, the spring-back is done by using both experimental and simulation using FEA software which is ABAQUS 6.7. The material use in this project is mild steel with 1 mm thickness. The size of the specimen is 100 mm x 100 mm. The experimental is done fist follow by the simulation. The specimen required in this project is 10 specimens. The Profile Projector machine is use to measure the angle of the sheet metal in the experiment. In the simulation, 2D drawing of the model have been made using ABAQUS 6.7. The punch, die and the sheet metal is main part in the drawing. The sheet metal then is defined as a rigid body in the software. The meshing has been done to sheet metal with 0.5 mm of the mesh size. After all the simulation is done, several node has been taken to measure the angle by using AutoCAD software. 8 nodes is taken an then transfer it to the AutoCAD software. The result from both experimental and simulation then be compared. The spring-back value in experimental is 62.3° while in the simulation the value is 62°.